Nanoscale chemical imaging using tip-enhanced Raman spectroscopy - Kumar, Naresh; Weckhuysen, Bert M; Wain, Andrew J; Pollard, Andrew J (Nature protocols, 2019)
Confocal and surface-enhanced Raman spectroscopy (SERS) are powerful techniques for molecular characterization; however, they suffer from the drawback of diffraction-limited spatial resolution. Tip-enhanced Raman spectroscopy (TERS) overcomes this limitation and provides chemical information at length scales in the tens of nanometers. In contrast to alternative approaches to nanoscale chemical analysis, TERS is label free, is non-destructive, and can be performed in both air and liquid environments, allowing its use in a diverse range of applications. Atomic force microscopy (AFM)-based TERS is especially versatile, as it can be applied to a broad range of samples on various substrates. Despite its advantages, widespread uptake of this technique for nanoscale chemical imaging has been inhibited by various experimental challenges, such as limited lifetime, and the low stability and yield of TERS probes. This protocol details procedures that will enable researchers to reliably perform TERS imaging using a transmission-mode AFM-TERS configuration on both biological and non-biological samples. The procedure consists of four stages: (i) preparation of plasmonically active TERS probes; (ii) alignment of the TERS system; (iii) experimental procedures for nanoscale imaging using TERS; and (iv) TERS data processing. We provide procedures and example data for a range of different sample types, including polymer thin films, self-assembled monolayers (SAMs) of organic molecules, photocatalyst surfaces, small molecules within biological cells, single-layer graphene and single-walled carbon nanotubes in both air and water. With this protocol, TERS probes can be prepared within ~23 h, and each subsequent TERS experimental procedure requires 3-5 h.